VD_FINDINFO Jug / 2021 / 87 vom 25. März 2021 - VD Tribunal cantonal (2021)
PRÉVOYANCE PROFESSIONNELLE, PARTAGESENS GÉNÉRAL, DIVORCE, DÉCISION EXÉCUTOIRE | 122 CC, 123 CC, 124e CC, 22 LFLP, 22a LFLP, 7 OLP, 8a OLP